β3 phosphorylation in autism spectrum disorders and neurosteroid activity. - Vien, Thuy. (2017)
Abstract: Alterations in GABAAR β3 expression and function are linked to autism spectrum disorders (ASDs). Protein kinase C (PKC)-mediated phosphorylation of the β3 subunit on serine residues 408/9 (S408/9) shapes its membrane expression and GABAergic inhibition. To evaluate whether dysregulation of this process was involved in ASDs we assessed β3 phosphorylation in Fmr1 knockout mice, a widely accepted model of ASDs. The Fmr1 knockout mouse is a mouse model for Fragile X syndrome, a genetic disorder involving the Fmr1 gene caused by an expansion of unstable trinucleotide repeats that result in decreased or abolished FMRP protein expression. Fmr1 knockout mice exhibited an increase in S408/9 phosphorylation and phasic inhibition along with significant deficits in tonic inhibition. In transgenic S408/9A knock-in mice where S408/9 were mutated to alanines, parallel modifications in GABAergic inhibition were observed. In addition, S408/9A mice exhibited an increase in dendritic spine morphology, increased repetitive-like behavior, and deficits in social interaction, prominent features of ASDs. Our findings suggest that changes in β3 phosphorylation may contribute to the pathophysiology of ASDs. Along with influencing GABAAR expression and function, PKC-mediated phosphorylation has been associated with neurosteroid action on extrasynaptic GABAARs that mediate tonic inhibition. In the dentate gyrus region of the hippocampus, tonic inhibition is mediated by GABAARs composed of α4β3δ subunits. Previously, we established that the neurosteroid allotetrahydrodeoxycorticosterone (THDOC) increased the PKC-dependent phosphorylation of α4 which led to an increase in its surface accumulation and tonic conduction. In S408/9A mice the THDOC-mediated increase in α4 surface expression and tonic conduction were abolished. Additionally, the anticonvulsant and hypnotic/anesthetizing properties of THDOC were diminished in S408/9A mice compared to WT controls. Collectively, our findings suggest a critical role for β3 phosphorylation in neurosteroid sensitivity.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Pharmacology & Experimental Therapeutics.; Advisor: Stephen Moss.; Committee: Jamie Maguire, Chris Dulla, Margery Beinfeld, Paul Davies, and David Clapham.; Keywords: Neurosciences, and Pharmacology.